Changes in the incidence and uptake of reproductive surgery versus in vitro fertilisation in Australia between 2001 and 2015: A population‐based study. (28th November 2018) - Foster, Leon; Robson, Stephen J.; Yazdani, Anusch; O'Shaughnessy, Pauline Y.
Abstract : Objective: Improvements in success rates of assisted reproduction led to predictions that infertility surgery in both women and men would become extinct in developed countries. We sought to identify the changes in reproductive surgery that occurred between 2001 and 2015 to determine whether these predictions have been accurate. Design: The Australian Institute of Health and Welfare (AIHW) national procedural dataset and the Australian Medicare Benefits Scheme (MBS) claims database were searched for procedure data for male and female reproductive surgery and assisted reproduction from January 2001 to December 2015. The denominators were based on annual point estimates of the total population aged 25–44 years (female) and 25–55 years (male) from the Australian Bureau of Statistics (ABS). This dataset provides procedures undertaken but not their indications. Results: Over the study period the incidence of tubal surgery fell by 66%, vasectomy reversal by 33%, and surgical varicocoelectomy by 50%. In contrast, the rate of hysteroscopic myomectomy increased by 48%, hysteroscopic septoplasty by 125%, and laparoscopy for severe endometriosis increased by 84%. In vitro fertilisation oocyte retrievals increased by 90%. The rate of abdominal myomectomy was unchanged. Conclusion: Fertility surgery is not dead but has evolved.